2022
DOI: 10.3389/fphar.2022.919567
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-4 and -5 Biology in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory disease of the gastrointestinal tract, associated with high levels of inflammatory cytokine production. Human caspases-4 and -5, and their murine ortholog caspase-11, are essential components of the innate immune pathway, capable of sensing and responding to intracellular lipopolysaccharide (LPS), a component of Gram-negative bacteria. Following their activation by LPS, these caspases initiate potent inflammation by causing pyroptosis, a lyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 177 publications
(293 reference statements)
0
4
0
Order By: Relevance
“…Upon LPS recognition in the cytoplasmatic milieu it comes to caspase oligomerization and cleavage of gasdermin-D (GSDMD), which permeabilizes cell membrane and induces pyroptosis [ 57 ]. Moreover, it has been presented that triggered caspases of a ‘non-canonical’ pathway can promote the activation of the ‘canonical’ NLR family pyrin domain-containing-3 (NLRP3) inflammasome and thus induce an inflammatory response, resulting in production of IL-1β and IL-18 [ 58 ]. Wang and colleagues also demonstrated increased levels of activated caspase-11 and NLRP3 in LPS-stimulated murine primary astrocytes [ 59 ].…”
Section: Cellular Recognition Of Lpsmentioning
confidence: 99%
“…Upon LPS recognition in the cytoplasmatic milieu it comes to caspase oligomerization and cleavage of gasdermin-D (GSDMD), which permeabilizes cell membrane and induces pyroptosis [ 57 ]. Moreover, it has been presented that triggered caspases of a ‘non-canonical’ pathway can promote the activation of the ‘canonical’ NLR family pyrin domain-containing-3 (NLRP3) inflammasome and thus induce an inflammatory response, resulting in production of IL-1β and IL-18 [ 58 ]. Wang and colleagues also demonstrated increased levels of activated caspase-11 and NLRP3 in LPS-stimulated murine primary astrocytes [ 59 ].…”
Section: Cellular Recognition Of Lpsmentioning
confidence: 99%
“…Assaying key protein molecules on three classical pathways of ERS-induced apoptosis showed that TP could regulate the CHOP /GADD153 gene activation transcriptional pathway and JNK activation pathway to suppress ERS. In the caspase12 pathway, caspase-12 is currently only available as a clone in the mouse, and caspase-12 in humans loses its role in regulating apoptosis due to genetic mutations, while it was previously reported that caspase-4, its homologous isomer, may play the same role [16] . Thus, caspase-4 was selected as an observation, but its expression was not observed, which caused much confusion and needs to be further explored in subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…As LPS induces the expression of CASP5 and activates caspase-5 within the noncanonical inflammasome, the primary function of caspase-5 is the initiation or amplification of the cellular response to LPS [74,75]. Infections with Gram-negative bacteria, such as Escherichia coli and Vibrio cholerae, can cause lethal diseases [34], and the appropriate initiation of an antibacterial defense counteracts disease both in mouse models and humans.…”
Section: Roles Of Caspase-5 In Human Diseasesmentioning
confidence: 99%
“…Gram-negative bacteria from the intestine can enter the tissue if the epithelial barrier is disturbed in IBD. Subsequently, cell-invasive bacteria activate caspase-4 and -5 [75,78,79], which are implicated in the development of chronic, relapsing inflammation. The growth of Legionella pneumophila, the causative agent of Legionnaires' pneumonia, in human macrophages was restricted by the ectopic expression of caspase-5.…”
Section: Roles Of Caspase-5 In Human Diseasesmentioning
confidence: 99%